PENGARUH CORPORATE GOVERNANCE DAN MANAJEMEN RISIKO TERHADAP ISLAMICITY PERFORMANCE INDEX PADA BANK UMUM SYARIAH TAHUN 2014-2018 - ASTI SALAMAH, SILKA; KUSUMANINGTIAS, ROHMAWATI (Jurnal Akuntansi AKUNESA, 2019)
This study aims to examine the effect Corporate Governance and Risk Management on the measured Islamicity Performance Index using four ratios, namely Profit Sharing Ratio, Equitable Distribution Ratio, Zakat Performance Ratio, and Islamic Income vs Non Islamic Income Ratio. This studies uses Canonical Correlation test. The research sample is 12 Sharia Commercial Banks (BUS) registered at Bank Indonesia in study period 2014-2018. The result of the study show that Corporate Governance has an effect on the Profit Sharing Ratio and Zakat Performance Ratio. While Risk Management proxyed with NPF has effect on the Profit Sharing Ratio and Zakat Performance Ratio. While FDR has no effect on Profit Sharing Ratio and, Zakat Performance Ratio. Keywords: Corporate Governance;Risk Management;Islamicity Performance Index; Sharia Commercial Banks.